Evaluation of thyroid disorders in abnormal uterine bleeding - Sharma, Priyanka; Patil, Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Abnormal uterine bleeding(AUB) is a common clinical presentation in gynecology. Alteration in thyroid hormones level has been associated with menstrual disturbances. This study is aimed to know the prevalence of thyroid disorders amongst AUB patients and also the different patterns of menstrual abnormalities associated with thyroid disorders. Methods: 100 Patient of clinically diagnosed AUB were taken from gynecology OPD. All the patients from 19 to 45 age groups presenting with menstrual disturbances were tested for thyroid function by measuring ST3, ST4, and S.TSH. Results: Out of 100 women of AUB, majority were in the age group of 31-40 years (38%), 54% were multiparous and 44% presented with menorrhagia. 65% were euthyroid, 17% had subclinical hypothyroidism, 15% had overt hypothyroidism and 3% were diagnosed as hyperthyroid. Subclinical hypothyroidism, overt hypothyroidism and hyperthyroidism were detected mostly in the age group of 31-40 years. The commonest bleeding abnormalities in hypothyroid patient were menorrhagia and polymenorrhoea. While most of the hyperthyroid cases were oligomenorrhoic. Conclusions: The study concludes that biochemical evaluation of thyroid function is an easy, reliable method and should be made mandatory in all cases of AUB.